Improving patient health engagement with mobile texting: A pilot study in the head and neck postoperative setting. Issue 5 (6th March 2017) - Sosa, Alan; Heineman, Nathan; Thomas, Kimberly; Tang, Kai; Feinstein, Marie; Martin, Michelle Y.; Sumer, Baran; Schwartz, David L.
ABSTRACT: Background: Cell phone ownership is nearly universal. Messaging is one of its most widely used features. Texting‐based interventions may improve patient engagement in the postoperative setting, but remain understudied. Methods: Patients were recruited before discharge from the hospital and received automated daily texts for 1 week providing information about expected recovery. Patients were encouraged to text questions to providers, which were triaged for intervention. Web‐based surveys solicited patient feedback about the platform. Results: Thirty‐two patients were approached, and 23 patients (72%) were enrolled in the study. All study patients texted their providers, although frequency (median, 7 texts; range, 2–44 texts) varied. Unmarried patients and those facing surgical complications used the platform more frequently. Mean patient satisfaction with the platform was high (mean, 3.8 on a 4‐point Likert scale). Conclusion: Text messaging seems feasible in the acute postoperative setting and potentially improves engagement of patients with head and neck cancer. Further study is warranted to confirm scalability and impact. © 2017 Wiley Periodicals, Inc. Head Neck 39: 988–995, 2017